Rediscovery of Crematogaster subgenus Colobocrema (Hymenoptera, Formicidae) in Southeast Asia - Yamane, Seiki; Tanaka, Hiroshi O.; Itioka, Takao (Zootaxa, 2011)
The Crematogaster subgenus Colobocrema was established to include the single species C. cylindriceps Wheeler, based on a single queen from the Philippines. We discovered a species close to or the same as C. cylindriceps in Borneo and provide descriptions of the queen, worker and male. This species lives in live climber plants of secondary and primary rainforests. The phragmotic morphology characterising the queen caste is considered an adaptation to a stem-inhabiting life style.